(untitled) - Clark, Eve V. (Cambridge, 2003)
This study takes a comprehensive look at where and when children acquire a first language. It integrates social and cognitive approaches to how children analyze, understand, and produce sounds, words, and sentences as they learn to use language to cooperate and achieve goals. A usage-based approach to considering what children learn emphasizes pragmatic factors in language use, and includes research on word-formation, and on bilingualism and dialect-choice.
Keywords: Language acquisition; Tiếp thu ngôn ngữ